Dataset for A Novel Spectroscopic Approach for Vaseline Quality Discrimination - Fliedner, Niels Hendrik; Lohweg, Volker; Pein-Hackelbusch, Miriam
This dataset contains spectroscopic measurement data and Orange project files used in the INDIN 2023 paper "A Novel Spectroscopic Approach for Vaseline Quality Discrimination".